2005
DOI: 10.1111/j.1365-2621.2005.tb07114.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of End-point Temperature and Degree of Doneness on Sensory and Instrumental Flavor Profile of Beefsteaks

Abstract: : Beef M. longissimus thoracis et lumborum was used to investigate the effects of 6 end‐point temperatures on flavor and texture. Steaks cooked to medium temperature were associated with 4‐heptanolide, whereas those cooked to higher temperatures were associated with pyrazines and hexanol. These steaks were also associated with flavor attributes, such as roasted, burnt, and beefy. However, consumers did not find differences in flavor liking of steaks (P > 0.05) cooked to 6 end‐point temperatures. Although stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…Juiciness ratings have been shown to have dramatic decreases (16 to 70%) when DOD was increased from lower endpoint temperatures (55 to 60°C) to higher endpoint temperatures (77 to 90°C) in multiple studies (Parrish et al, 1973;Cross et al, 1976;Lorenzen et al, 2005;Lucherk et al, 2016). Observed tenderness decreases have been similar, with decreased tenderness ratings of 20 to 58% when final endpoint temperature is increased over the same range (Parrish et al, 1973;Cross et al, 1976;Lorenzen et al, 2005). The current study shows a decrease in palatability similar to previous research.…”
Section: Degree Of Donenesssupporting
confidence: 75%
See 3 more Smart Citations
“…Juiciness ratings have been shown to have dramatic decreases (16 to 70%) when DOD was increased from lower endpoint temperatures (55 to 60°C) to higher endpoint temperatures (77 to 90°C) in multiple studies (Parrish et al, 1973;Cross et al, 1976;Lorenzen et al, 2005;Lucherk et al, 2016). Observed tenderness decreases have been similar, with decreased tenderness ratings of 20 to 58% when final endpoint temperature is increased over the same range (Parrish et al, 1973;Cross et al, 1976;Lorenzen et al, 2005). The current study shows a decrease in palatability similar to previous research.…”
Section: Degree Of Donenesssupporting
confidence: 75%
“…Many authors have reported as DOD increases, WBSF values also increase (Lorenzen et al, 2005;Gomes et al, 2014;Lucherk et al, 2016). It is also well documented that as internal temperature increases, the percentage of cooking loss increases (Parrish et al, 1973;Luchak et al, 1998;Lorenzen et al, 2005).…”
Section: Degree Of Donenessmentioning
confidence: 92%
See 2 more Smart Citations
“…The roasting of meat enhances oxidation process compared to other methods of heat treatment due to prolonged meat exposure to high temperatures (Domínguez et al, 2014). A strong correlation exists between heating temperature, concentration of free amino acids, carnosine, IMP, pyrazines and hexanol and the intensity of taste of roasted, burnt and cooked beef (Lorenzen et al, 2005).…”
Section: Factors Affecting Changes In Volatile Compoundsmentioning
confidence: 99%